2020
DOI: 10.5582/irdr.2020.03006
|View full text |Cite
|
Sign up to set email alerts
|

Update on cystine stones: current and future concepts in treatment

Abstract: cystinuria, urolithiasis, novel therapy, cystine stone, tiopronin, D-penicillamine Cystine stones are relatively uncommon compared with other stone compositions, constituting just 1% to 2% of adult urinary tract stone diseases, and accounting for up to 10% of pediatric stone diseases. Two responsible genes of cystinuria have been identified, the SLC3A1 and the SLC7A9. Cystinuria is diagnosed by family history, stone analysis, or by measurement of urine cystine excretion. Current treatments for cystinuria inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 70 publications
1
32
0
1
Order By: Relevance
“…Dietary sodium restriction seems to be an important component of the therapeutic strategy in cystinuric people because dietary sodium may enhance cystinuria [ 94 , 95 ]. Dietary sodium in canine therapeutic diets should be limited to less than 0.3% dry matter [ 6 ].…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Dietary sodium restriction seems to be an important component of the therapeutic strategy in cystinuric people because dietary sodium may enhance cystinuria [ 94 , 95 ]. Dietary sodium in canine therapeutic diets should be limited to less than 0.3% dry matter [ 6 ].…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…Regulators acknowledge the need for accelerating the rare disease drug development pathway and may approve a biomarker endpoint measure in the absence of validated endpoint measures for the intended patient population. Examples of rare disease drugs that have received approval based on biomarker primary endpoints include tiopronin for cystinuria (biomarker: reduction in urinary excretion of cystine) sapropterin dihydrochloride for phenylketonuria (reduction in plasma phenylalanine), agalsidase beta for Fabry disease (reduction of globotriaosylceramide storage granules in biopsied kidney interstitial capillaries), imiglucerase for Gaucher disease type I (composite of biomarker endpoints, including haemoglobin and platelet count) and sebelipase alfa for lysosomal acid lipase deficiency (normalisation of serum alanine aminotransferase levels) [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current preventive treatments for cystinuria include increased fluid intake to increase cystine solubility and limiting sodium and protein intake to decrease cystine excretion. Pharmacologic therapy such as alkalizing agents and cystine-binding thiol drugs may also be effective [ 4 ]. Although it has been reported that patients taking cystine-binding thiol drugs have a high quality of life, there are adverse effects and poor compliance with the drugs [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that patients taking cystine-binding thiol drugs have a high quality of life, there are adverse effects and poor compliance with the drugs [ 5 , 6 ]. Despite these preventive measures, cystine stone formers frequently experience stone-related episodes and surgical intervention [ 4 ]. Many patients suffer from renal insufficiency because of the stone-recurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation